AAV8-mediated In Vivo overexpression of miR-155 enhances the protective capacity of genetically attenuated Malarial parasites - Hentzschel, Franziska; Börner, Kathleen; Heiß, Kirsten; Knapp, Bettina; Sattler, Julia M.; Kaderali, Lars; Müller, Ann-Kristin; Grimm, Dirk (Molecular therapy, 2014)
Malaria, caused by protozoan Plasmodium parasites, remains a prevalent infectious human disease due to the lack of an efficient and safe vaccine. This is directly related to the persisting gaps in our understanding of the parasite's interactions with the infected host, especially during the clinically silent yet essential liver stage of Plasmodium development. Previously, we and others showed that genetically attenuated parasites (GAP) that arrest in the liver induce sterile immunity, but only upon multiple administrations. Here, we comprehensively studied hepatic gene and miRNA expression in GAP-injected mice, and found both a broad activation of IFNγ-associated pathways and a significant increase of murine microRNA-155 (miR-155), that was especially pronounced in non-parenchymal cells including liver-resident macrophages (Kupffer cells). Remarkably, ectopic upregulation of this miRNA in the liver of mice using robust hepatotropic adeno-associated virus 8 (AAV8) vectors enhanced GAP's protective capacity substantially. In turn, this AAV8-mediated miR-155 expression permitted a reduction of GAP injections needed to achieve complete protection against infectious parasite challenge from previously three to only one. Our study highlights a crucial role of mammalian miRNAs in Plasmodium liver infection in vivo and concurrently implies their great potential as future immune-augmenting agents in improved vaccination regimes against malaria and other diseases.
Gesehen am 21.10.2020